Soul care in the hospital nursing context: an analysis based on Transpersonal Caring - Emanuelle Caires Dias Araújo Nunes; Hévellin da Silva Santos; Gleica Afonso Dutra; Juliana Xavier Pinheiro da Cunha; Regina Szylit (SciELO, 2020)
Abstract Objective: To unveil spirituality in the care process of nursing professionals in the hospital context under the lens of Transpersonal Caring. Method: A descriptive-exploratory study implementing a qualitative approach conducted with professionals from the nursing team in a general hospital in Bahia, using a semi-structured interview submitted to the content analysis technique and analyzed from the perspective of the Theory of Transpersonal Caring theoretical framework. Results: There were 16 professionals who participated. It was found that the nursing team perceives the patient and family's demand for spiritual care, and sometimes even has experiences and suggestions for interventions, especially those which cultivate faith and spirituality, but this does not happen with most of these professionals who demonstrate difficulties, unpreparedness and fear of taking on such care responsibility. Conclusion: There is a need to develop better interaction/spiritual care skills by nursing professionals in the challenging context of the search for meaning, faith and hope mobilized by the disease experience. The Systematization of Spiritual Nursing Care and Transpersonal Caring stand out as appropriate devices, which provide consistent subsidies for undertaking spiritual care.